2013
DOI: 10.1007/s00122-013-2127-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of two genes conferring resistance to Phytophthora sojae in a soybean landrace PI 567139B

Abstract: Phytophthora root and stem rot (PRR), caused by the soil-borne oomycete pathogen Phytophthora sojae, is one of the most destructive diseases of soybean. PRR can be effectively controlled by race-specific genes conferring resistance to P. sojae (Rps). However, the Rps genes are usually non-durable, as populations of P. sojae are highly diverse and quick to adapt, and can be overcome 8-15 years after deployment. Thus, it is important to identify novel Rps genes for development of resistant soybean cultivars. PI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 35 publications
1
79
0
3
Order By: Relevance
“…The green line refers to the physical distance between bin249 and bin283, and the red line refers to the fine mapping region. (C) Physical position of the mapped region of RpsHN on chromosome 3 (Lin et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…The green line refers to the physical distance between bin249 and bin283, and the red line refers to the fine mapping region. (C) Physical position of the mapped region of RpsHN on chromosome 3 (Lin et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Detection of Mature miRNA, MIRNA Gene, and PEG Expression Small RNAs generated from the susceptible cultivar Williams and its nine NILs (Lin et al, 2013;Zhao et al, 2015) were used to estimate relative abundance (or levels of accumulation) of mature miRNAs. To detect the transcripts of MIRNAs embedded in the host PEGs and splicing sites of the host PEGs, RNA-seq data from 28 samples of soybean (Glycine max) tissues at different developmental stages previously generated (Shen et al, 2014) were retrieved and reanalyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Tolerance to Phytophthora root rot is multi-genic due to the presence of several races of pathogen and so far 20 Rps (resistance to P. sojae ) loci including 26 alleles have been detected on four different chromosomes i.e., Gm03, Gm13, Gm16, and Gm18 (Li et al, 2016a). Lin et al (2013) have identified two Rps genes, RpsUN1 on chromosome 3 and RpsUN2 on chromosome 16 from a soybean landrace PI 567139B, which together confer complete resistance to 16 P. sojae races/isolates. Li et al (2016a), further narrowed RpsUN1 and RpsUN2 , to a 151 kb region that harbors five genes including three disease resistance (R)-like genes, and a 36 kb region that contains four genes, all of which are of the typical R-like genes, respectively.…”
Section: Qtlomics: Qtls To Genes In Soybeanmentioning
confidence: 99%